False negatives in thyroid cytology: Impact of large nodule size and follicular variant of papillary carcinoma. (4th January 2013) - Mehanna, Rania; Murphy, Michael; McCarthy, Julie; O'Leary, Gerard; Tuthill, Antoinette; Murphy, Matthew S.; Sheahan, Patrick
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Fine‐needle aspiration (FNA) cytology is well established in the diagnosis of thyroid nodules. However, false‐negative rates for malignancy of 3% to 10% are reported. The purpose of the present study was to investigate the impact of nodule size and follicular variant of papillary carcinoma (FVPTC) on false‐negative FNA rates in thyroid nodules and on malignancy rates in nodules with indeterminate cytology. Study Design Retrospective study. Methods A total of 765 consecutive ultrasound‐guided FNAs were reviewed. Histological correlation was available in 262 cases. Results The overall sensitivity of FNA for malignancy was 84%, and the false‐negative rate 9.1%. Nodules ≥3 cm were significantly more likely to ultimately be diagnosed as cancer by histology than nodules <3 cm (14% vs. 6.8%, P = .006); however, they were also significantly more likely to undergo surgery than smaller nodules (P < .0001). Among the surgical series, the false‐negative rate was 10.9% in nodules ≥3 cm and 6.1% in nodules <3 cm (P = .71). Most false negatives were due to FVPTC. FVPTC was significantly more likely to be missed by preoperative cytology than conventional or other variants of papillary carcinoma (P < .001). Among cases with indeterminate cytology, nodule size and Thy‐3f versus Thy‐3a subclassification did not have any significant impact on likelihood of malignancy. Conclusions The sensitivity of FNA for detection of FVPTC is reduced compared to conventional papillary carcinoma. The impact of nodule size is not significant. Level of Evidence 4.